PENENTUAN MODEL ANTRIAN BUS ANTAR KOTA DI TERMINAL MANGKANG - Ispriyanti, Dwi; Sugito, Sugito (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2012)
In daily activities, we often face in a situation of queueing. The Queue is dull. Most people have experienced in a queue situation or a waiting situation. It is a part of the state that occurs in a series of operations that are random in a service facility. The Queue can be found easily in a human life, for example bus queue in Terminal Mangkang. It means that a bus wait to be dispatched and from the bus that will go to the service station. Therefore make an arrival and departure of buses not on schedule which resulted in the accumulation of customers in the terminal. To analyze the extent of the effectiveness of terminal Mangkang particularly inter-city terminal Queue theory it is used in the service system in the terminal. Keywords: Queue, Terminal Mangkang